Peran Foto Produk Sebagai Branding UMKM di Kelurahan Gebang Putih - Roziana Febrianita; Fadhiatus Zahro; Melyssa Safira Anwar; Akmal Nugraha Ramadhan (BADAN PENERBIT STIEPARI PRESS, 2023)
Micro, Small, and Medium Enterprises or MSMEs can be said to be the driving force for the national economy and employment. Its contribution to Indonesia's economic growth reached 99% of all business units. The community service team from UPN